A review of angel investing research: analysis of data and returns in the US and abroad. Issue 4 (3rd October 2016) - McDonald, Michael B.; DeGennaro, Ramon P.
Abstract : Purpose: The purpose of this paper is to examine the literature on angel investors. Research on angel investors is sparse because data are sparse. Most comprehensive studies of angel investors have focused on the USA and UK. In these studies, definitions of angel investors and estimates of returns on angel investments vary dramatically. What can one make of this wide range of reported returns? Design/methodology/approach: The authors examine the literature and find that the calculations of reported results are vague. Findings: Most researchers do not explicitly report if their estimates are equal-weighted or value-weighted, nor do they say whether the results are weighted by the duration of the investment. The authors show that the unit of analysis – investment, project or angel – affects interpretations. Practical implications: Limitations on the comparability between various studies of angel investing returns leave the current literature incomplete. They also offer opportunities for future study in the area. Originality/value: The authors are the first to examine the angel investing literature in a comprehensive fashion, comparing between various returns found across all major studies of the subject done to date.